Splenic Epidermoid Cyst - A Rare Case Managed in a private medical college hospital of Bangladesh (Bangladesh Journal of Medical Science, 2021)
Splenic cysts are rarely detected, and clinically diagnosed commonly as spleenomegaly . Thenature of the cyst could not be diagnosed pre-operatively because of its’ anatomical location andonly be confirmed by the histopathological assessments. These cysts are found as a sequel ofsplenic infarct followed by the abscess formation. This is a very rare condition of a minor boy ofonly 10 years’ old who presented with a hugely enlarged spleen. The common investigation(s)did not prove that it was in the haematological conditions. Ultrasonogram (USG) investigationshows spleenomegaly due to the cystic lesion. CT scan of the abdomen showed large andwell defined cystic mass which was 13.4cmX7.9cmX15.3cm in size, multi-loculated, septated,sharply demarcated as such well delineated cyst. After necessary preparation like vaccination,blood grouping, cross matching and other fitness, laparotomy and total spleenectomy was doneas the cyst occupied most of the Splenic tissue. The post operative recovery was uneventful andthe final diagnosis was confirmed by histopatholgical examinations as epidermoid cyst of thespleen. The patient was followed up for two consecutive months and not a single complicationwas noticed.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.177-180